Inductance Simulators and Their Application to the 4th Order Elliptic Lowpass Ladder Filter Using CMOS VD-DIBAs - Winai Jaikla; Sirigul Bunrueangsak; Fabian Khateb; Tomasz Kulej; Peerawut Suwanjan; Piya Supavarasuwat (My University, 2021)
This paper presents inductance simulators using the voltage differencing differential input buffered amplifier (VD-DIBA) as an active building block. Three types of inductance simulators, including floating lossless inductance, series inductance-resistance, and parallel inductance-resistance simulators, are proposed, in addition to their application to the 4th order elliptic lowpass ladder filter. The simple design procedures of these inductance simulators using a circuit block diagram are also given. The proposed inductance simulators employ two VD-DIBAs and two passive elements. The complementary metal oxide semiconductor (CMOS) VD-DIBA used in this design utilizes the multiple-input metal oxide semiconductor (MOS) transistor technique in order to achieve a compact and simple structure with a minimum count of transistors. Thanks to this technique, the VD-DIBA offers high performances compared to the other CMOS structures presented in the literature. The CMOS VD-DIBAs and their applications are designed and simulated in the Cadence environment using a 0.18 µm CMOS process from Taiwan semiconductor manufacturing company (TSMC). Using a supply voltage of ±0.9 V, the linear operation of VD-DIBA is obtained over a differential input range of −0.5 V to 0.5 V. The lowpass (LP) ladder filter realized with the proposed inductance simulators shows a dynamic range (DR) of 80 dB for a total harmonic distortion (THD) of 2% at 1 kHz and a 1.8 V peak-to-peak output. In addition, the experimental results of the floating inductance simulators and their applications are obtained by using VD-DIBA constructed from the available commercial components LM13700 and AD830. The simulation results are in agreement with the experimental ones, confirming the advantages of the inductance simulators and their application.
Keywords: Equivalent series inductance; Analog and Mixed-Signal Circuit Design